PENGARUH PENAMBAHAN FLY ASH TERHADAP KUAT TEKAN DAN PENYERAPAN AIR BATA RINGAN - Mulyati Mulyati; Yoga Pradana; Arman A Arman A (Ensiklopedia Research and Community Service Review, 2026)
This study aims to analyze the effect of adding fly ash on the compressive strength and water absorption of lightweight bricks. The use of fly ash as an additional material is one of the efforts to improve the quality of lightweight brick. The fly ash used is waste from burning coal at a Steam Power Plant as an additional material for lightweight brick mixtures with variation of 0%, 15%, and 30% of the cement weight. The test specimens were made using the mixing, molding, and curing methods according to SNI 8640:2018. Compressive strength and water absorption test were carried out after the test specimens reached the age of 28 days. The results of the study show that the addition of fly ash has an effect on the compressive strength and water absorption of lightweght brick. In a 30% fly ash mixtures, compressive strength can increase to 187.7%, and water absorption becomes lower (from 21.99% to 17.89%). Based on research results, the addition of fly ash up to 30% can produce a balance between high compressive strength and low water absorption, so that fly ash has potential to be an alternative mixed material in the production of lihgtweght bricks.Keywords: Lightweight Brick, Fly Ash, Compressive Strength, Water Absorption